BIOMECHANICAL COMPARATIVE STUDY BETWEEN TENSION BAND WIRING, DOUBLE ENDO BUTTON AND HOOK PLATE FOR ACROMIOCLAVICULAR JOINT INJURY - Erwin Ramawan; Jifaldi Afrian MDS (Journal Orthopaedi and Traumatology Surabaya)
Background: The treatment for acromioclavicular joint injury are debatable, there are fixation options include tension band wiring, AC joint reconstruction and hook plate These fixations are capable of providing a stable fixation, but controversy still exists that mentions the superiority of each of these fixations